ECP versus ruxolitinib in steroid-refractory acute GVHD – a retrospective study by the EBMT transplant complications working party - Penack, Olaf; Peczynski, Christophe; Boreland, William; Lemaitre, Jessica; Afanasyeva, Ksenia; Kornblit, Brian; Jurado, Manuel; Martinez, Carmen; Natale, Annalisa; Pérez-Simón, Jose Antonio; Brunello, Lucia; Avenoso, Daniele; et al. (Frontiers in Immunology, 2023)
Extracorporal Photophoresis (ECP) is in clinical use for steroid-refractory and steroiddependent acute GVHD (SR-aGVHD). Based on recent Phase-III study results, ruxolitinib has become the new standard of care for SR-aGVHD. Our aim was to collect comparative data between ruxolitinib and ECP in SR-aGVHD in order to improve the evidence base for clinical decision making. We asked EBMT centers if they were willing to participate in this study by completing a data form (Med-C) with detailed information on GVHD grading, -therapy,dosing, -response and complications for each included patient. 31 centers responded positively (14%) and we included all patients receiving alloSCT between 1/2017-7/2019 and treated with ECP or ruxolitinib for SR-aGVHD grades II-IV from these centers. We identified 53 and 40 patients with grades II-IV SR-aGVHD who were treated with ECP and ruxolitinib, respectively.